Digital Automatic Coupling (DAC) – Project Information (Current Problems in Rail Vehicles, 2025)
Description of the DACFIT project in relation to all work areas and activities related to DAC within Europe's Rail Flagship Project 5. Experiences from the analysis of the possibilities of integrating DAC into the existing fleet of freight wagons and locomotives, which is being addressed by the VÚKV in cooperation with the project partners. Discussion of the broader context regarding future intelligent freight wagon options.
Keywords: digital automatic couplers; freight wagon; locomotive